42 UMP staff cycles 46 km to complete the cycling mission - Nor Salwana, Mohammad Idris (2020)
PEKAN, 28 November 2020 - Indirect rainy weather prevented 42 Universiti Malaysia Pahang (UMP) staff from cycling for 4.6 kilometres in the UMP Cycling Challenge 2020 Competition organized by the UMP Sports and Culture Centre recently.